Transcutaneous bilirubin nomogram for Taiwanese newborns - A single center study - Tung-Hua Chen; Yung-Chieh Lin; Yuh-Jyh Lin; Chyi-Her Lin (Elsevier, 2019)
Background: Hour-specific bilirubin nomogram has been recommended to predict postdischarge hyperbilirubinemia in newborns. However, it may not be applicable in Taiwan due to ethnic differences. The aim of this study was to construct a 12-h specific transcutaneous bilirubin (TCB) nomogram in newborns for clinical reference. Methods: We prospectively enrolled full term or late preterm neonates born in a tertiary care hospital between October 2013 and July 2014. The exclusion criteria included chromosome anomaly, glucose-6-phosphate dehydrogenase deficiency, and receiving phototherapy within 60 h after birth. TCB measurements were performed by a single technician using the Bilichek device, and measured every 12 h until neonates were discharged. Patient data including sex, delivery mode, gestational age, body weight with daily change, and feeding pattern were collected for analysis. A TCB nomogram was constructed with 40th, 75th, and 95th percentile lines. Results: A total of 498 newborns were enrolled, and the characteristics between the hyperbilirubinemia and nonhyperbilirubinemia groups were not different. The mean TCB curve revealed that the peak TCB level was 14.2 ± 2.9 mg/dL at 100.6 ± 3.6 h of age. The peak 95th percentile TCB level was 19.4 mg/dL at 121.9 ± 5 h of age. Mean TCB levels increased at a rate of 0.01-0.21 mg/dL/h initially, followed by a decrease after 96-108 h of age. Twenty newborns (4%) were diagnosed with hyperbilirubinemia. Regarding TCB distribution, 11 of 60 (18%) had peak TCB levels above the 95th percentile, 5 of 151 (3%) had TCB levels between the 75th and 95th percentile, 4 of 200 (2%) had levels between the 40th and 75th percentiles, and none had a level below the 40th percentile. Conclusion: A 12-h specific TCB nomogram could be a useful reference for workup for hyperbilirubinemia, particularly when it is above the 95th percentile line. Key Words: hyperbilirubinemia, nomogram, transcutaneous bilirubin